2012
DOI: 10.4236/psych.2012.329115
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory in Patients with Major Depressive Disorder

Abstract: Objective: Patients with major depressive disorder (MDD) have been reported to perform less well in neurocognitive tests than normal control subjects. The author tested the hypotheses that verbal working memory (WM) is predictive of the functional outcome in patients with MDD. Methods: In this naturalistic longitudinal study, the subjects consisted of 22 adult outpatients receiving paroxetine as antidepressant therapy. Functional outcome was rated on a scale of 0 (non-impaired) to 3 (severely impaired). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Two studies have associated working memory function with depression treatment outcome. 14,17 Similarly, it has been reported that lower attention predicts poorer response to depression treatment. 37 These findings suggest that patients who are less impaired in functions such as working memory and attention have a better prognosis, regardless of the type of treatment they are receiving.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Two studies have associated working memory function with depression treatment outcome. 14,17 Similarly, it has been reported that lower attention predicts poorer response to depression treatment. 37 These findings suggest that patients who are less impaired in functions such as working memory and attention have a better prognosis, regardless of the type of treatment they are receiving.…”
Section: Discussionmentioning
confidence: 93%
“…25 The BDI measures severity of depression and classifies results as minimal (score, 0-11), mild (score, [12][13][14][15][16][17][18][19], moderate (score, 20-35), or severe (score, 36-63).…”
Section: Instruments and Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation